A novel texture feature based multiple classifier technique for roadside vegetation classification. Issue 12 (15th July 2015) - Chowdhury, Sujan; Verma, Brijesh; Stockwell, David
Highlights Proposed technique use LBP based GLCM feature vector and multiple classifiers. We achieve over 92% accuracy for vegetation classification. Extensive experiments use 5-fold cross validation. The experiments were conducted on dense and sparse grasses. In future, extension will be done by introducing large dataset of grasses.